Prone positioning effect on tracheal intubation rate, mortality and oxygenation parameters in awake non-intubated severe COVID-19-induced respiratory failure: a review of reviews - Sepideh Tahsini Tekantapeh; Nader D. Nader; Morteza Ghojazadeh; Fatemeh Fereidouni; Hassan Soleimanpour (European Journal of Medical Research, 2024)
Abstract Background Prone positioning (PP) is a low-cost method with minimal risk to the patient that improves the oxygenation of patients with acute hypoxic respiratory failure (AHRF) due to COVID-19 pneumonia, thereby reducing their need for tracheal intubation (TI) and transferring to the intensive care unit (ICU). We aimed to overview the results of all previous systematic reviews and meta-analyses to examine the net effect of PP on oxygenation, the rate of TI and mortality in COVID-19 patients. Methods We searched PubMed, Scopus, Web of Science, Google Scholar, and Cochrane Library databases from December 2019 through 2022 without publication language restriction for systematic reviews and meta-analysis studies on PP vs. supine position (SP) in conscious patients with hypoxic respiratory failure COVID-19. After study selection, data were extracted from published meta-analyses and pooled by comprehensive meta-analysis (CMA) software version 2.2.064 to achieve effect sizes. They were analyzed for TI and mortality rates dichotomous variables, and the results were shown as pooled odds ratios (OR) with a 95% confidence interval (CI). Continuous variables such as oxygenation indices (PaO2/FiO2 and SpO2) were also analyzed, and the data were shown as mean differences (MD) with lower and upper CI. The level of statistical significance was set at p ≤ 0.05. Results Twelve systematic reviews and meta-analyses with 19,651 patients and six systematic reviews with 2,911 patients were included in this Review of Reviews (total: 22,562). PP treatment significantly reduced the rate of TI (OR = 0.639, %95 CI (0.492, 0.829); P-value = 0.001) and decreased mortality (OR = 0.363, %95 CI (0.240, 0.549), P-value < 0.001). There was no difference in PaO2/FiO2 (MD = 3.591[− 40.881, 48.062]; P-value = 0.874) and SpO2 percent (MD = 1.641[− 4.441, 7.723]; P-value = 0.597). Conclusion Prone positioning can be recommended in conscious ICU patients with COVID-19 pneumonia to reduce mortality and intubation. Systematic review registration: PROSPERO registration number: CRD42022326951. Registered 25 April 2022. Graphical Abstract